From alternative development to sustainable development: The role of development within the global drug control regime - Daniel Brombacher; Jan Westerbarkei (Journal of Illicit Economies and Development (JIED), 2019)
The concept of alternative development (AD) in international drug control has evolved over the past four decades, with several major milestones between the two United Nations General Assembly Special Sessions on the World Drug Problem (UNGASS) 1998 and 2016. However, it was not until UNGASS 2016 that the door for development-oriented thinking in international drug policy was pushed wide open. The Chapter VII of the UNGASS 2016 Outcome Document not only assigns a prominent role to AD, but also seeks to broaden the scope of development towards urban drug markets and drug trafficking, formerly exclusive realms of law enforcement and repressive measures of drug supply control. Therefore, in the field of development a major revolution has taken place through the unequivocal broadening of the scope of development within UN drug control, feeding directly into the much-needed approximation of the UN drug control system and the Sustainable Development Goals. The article sheds light on the evolvement of the German approach of alternative development that has been influential at the international level in the shaping of the global drugs and development nexus.
Keywords: 330; Alternative development; German approach; UNGASS 2016; Development-oriented drug policy; Development-oriented drug control